2017
DOI: 10.5114/pwki.2017.67994
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of closed-cell and hybrid-cell stent designs in carotid artery stenting: clinical and procedural outcomes

Abstract: IntroductionCarotid artery stenting (CAS) is a promising alternative to surgery in high-risk patients. However, the impact of stent cell design on outcomes in CAS is a matter of continued debate.AimTo compare the periprocedural and clinical outcomes of different stent designs for CAS with distal protection devices.Material and methodsAll CAS procedures with both closed- and hybrid-cell stents performed at our institution between February 2010 and December 2015 were analyzed retrospectively. Adverse events were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…Similarly, analysis of adverse outcome predictors in 828 patients randomised to the CAS arm of the International Carotid Stenting Study (ICSS), demonstrated that use of an open-cell stent conferred a statistically significant two-fold higher risk of stroke by 30 days than use of a closed-cell stent (relative risk (RR) = 1.92, 95% CI: 1.11–3.33) [ 48 ]. There are theoretical grounds and there is some moderate-scale evidence that hybrid stents, which combine the open-cell design advantage of high conformability (proximal and distal stent section) with the closed-cell design of the mid-section of the stent aimed to cover the plague, may be non-inferior to closed-cell stents [ 49 ].…”
Section: Evolution Of Carotid Revascularisation Strategies After Cresmentioning
confidence: 99%
“…Similarly, analysis of adverse outcome predictors in 828 patients randomised to the CAS arm of the International Carotid Stenting Study (ICSS), demonstrated that use of an open-cell stent conferred a statistically significant two-fold higher risk of stroke by 30 days than use of a closed-cell stent (relative risk (RR) = 1.92, 95% CI: 1.11–3.33) [ 48 ]. There are theoretical grounds and there is some moderate-scale evidence that hybrid stents, which combine the open-cell design advantage of high conformability (proximal and distal stent section) with the closed-cell design of the mid-section of the stent aimed to cover the plague, may be non-inferior to closed-cell stents [ 49 ].…”
Section: Evolution Of Carotid Revascularisation Strategies After Cresmentioning
confidence: 99%
“… 27 One of the most common complications of closed-cell stents is vasospasm at the distal side of the carotid artery, leading to slow flow. 28 …”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the open-cell or hybrid cell designs is to allow flexibility when used in patients with angulated or tortuous vessels. The results of a previously published study showed no significant difference in adverse event rates, including embolization following CAS, between the closed-cell stent group and the hybrid-cell stent group [11]. However, procedural internal carotid artery vasospasm more frequently occurred in the closed-cell stent group [11].…”
Section: Discussionmentioning
confidence: 99%